The national ignition facility: laser performance status and performance quad results at elevated energy. (18th December 2018) - Di Nicola, J.M.; Bond, T.; Bowers, M.; Chang, L.; Hermann, M.; House, R.; Lewis, T.; Manes, K.; Mennerat, G.; MacGowan, B.; Negres, R.; Olejniczak, B.; et al.
Abstract: The National Ignition Facility (NIF) at Lawrence Livermore National Laboratory, is the first of its kind megajoule-class laser facility with 192 beams capable of delivering over 1.8 MJ and 500TW of 351 nm light for high accuracy laser-matter interaction experiments. It has been commissioned and operated since 2009 to support a wide range of missions including the study of inertial confinement fusion, high energy density physics, material science, and laboratory astrophysics. In the first section of this paper we discuss the current status of laser performance obtained during the 408 target experiments completed in 2017. The performance spanned a wide range of laser energies, powers and pulse durations as requested for these target experiments. A special emphasis is given on energy delivery and cone power accuracy in the UV, as these are key parameters for successful experiments. In the second section of the paper, the results obtained during the 2017 performance quad campaign are briefly described. During this campaign a series of laser-only shots were taken to perform tests at elevated energies on a single NIF quad. These tests were designed to assess laser performance limits and operational costs against predictive models. This campaign culminated with the delivery of ~54 kJ of UV on a single quad of NIF, and 14 kJ on a single beam aperture, which are both to our knowledge the largest energies achieved to date for a neodymium-glass, frequency tripled architecture.